Development of Didactic Materials for Preschool Children with Different Sensory Perceptions - A. Komissarova, L.; V. Yakovleva, V. (International Journal of Engineering and Technology, 2018)
This article discusses the universal design in the subject environment. Universal design in the sphere of subject environment is a developing direction, which is necessary, especially in the field of education. Development of didactic materials for children with different sensory perceptions is proposed.Â Â